2002
DOI: 10.2460/javma.2002.220.477
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of platelet count recovery with use of vincristine and prednisone or prednisone alone for treatment for severe immune-mediated thrombocytopenia in dogs

Abstract: Administration of combined vincristine and prednisone is associated with more rapid increase in platelet numbers and shortened duration of hospitalization in dogs with IMT, compared with use of prednisone alone. Early use of vincristine seems warranted in dogs with severe primary IMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
117
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(130 citation statements)
references
References 10 publications
8
117
0
5
Order By: Relevance
“…The median platelet recovery time of 2.5 days for both groups in this study was similar to the recovery times reported in the treatment arms of both previous prospective studies evaluating VINC and hIVIG for treatment of presumptive ITP. 7,8 In a study evaluating hIVIG treatment of dogs with ITP, the median recovery time for dogs treated with hIVIG was 3.5 days 8 and in a study evaluating VINC as an adjunctive treatment for ITP, the median recovery time for dogs treated with VINC was 4.5 days. 7 The recovery times for both groups in this study were shorter than the glucocorticoid only arms of these previous prospective clinical trials, which were 7.5 days and 6.5 days for hIVIG and VINC, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The median platelet recovery time of 2.5 days for both groups in this study was similar to the recovery times reported in the treatment arms of both previous prospective studies evaluating VINC and hIVIG for treatment of presumptive ITP. 7,8 In a study evaluating hIVIG treatment of dogs with ITP, the median recovery time for dogs treated with hIVIG was 3.5 days 8 and in a study evaluating VINC as an adjunctive treatment for ITP, the median recovery time for dogs treated with VINC was 4.5 days. 7 The recovery times for both groups in this study were shorter than the glucocorticoid only arms of these previous prospective clinical trials, which were 7.5 days and 6.5 days for hIVIG and VINC, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In a study evaluating hIVIG treatment of dogs with ITP, the median recovery time for dogs treated with hIVIG was 3.5 days 8 and in a study evaluating VINC as an adjunctive treatment for ITP, the median recovery time for dogs treated with VINC was 4.5 days. 7 The recovery times for both groups in this study were shorter than the glucocorticoid only arms of these previous prospective clinical trials, which were 7.5 days and 6.5 days for hIVIG and VINC, respectively. The median duration of hospitalization of 4 days for the dogs in this study also was similar to that reported in the previous studies of hIVIG (4 days) and VINC (5 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, antiplatelet antibody testing is not routinely available in veterinary practice. The thrombocyte count cut-off to distinguish between ITP and disseminated intravascular coagulation (DIC) in dogs has been reported as 15 Â 10 9 /L (Rozanski et al 2002), although another study reported median thrombocyte counts of 32 Â 10 9 /L in dogs with ITP and 55 Â 10 9 /L in dogs with DIC (Botsch et al 2009). …”
Section: Differential Diagnosismentioning
confidence: 99%